2022
DOI: 10.3390/ani12030359
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporins and Animal Gamete Cryopreservation: Advances and Future Challenges

Abstract: Cryopreservation is globally used as a method for long-term preservation, although freeze-thawing procedures may strongly impair the gamete function. The correct cryopreservation procedure is characterized by the balance between freezing rate and cryoprotective agents (CPAs), which minimizes cellular dehydration and intracellular ice formation. For this purpose, osmoregulation is a central process in cryopreservation. During cryopreservation, water and small solutes, including penetrating cryoprotective agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 169 publications
0
6
0
1
Order By: Relevance
“…Targeted enrichment of valine was developed as per and was proved to be effective [ 78 ]. Ribeiro et al showed the genetically determined aquaporins expression difference may render the variation in cryotolerance [ 79 ]. These results are important for the identification of potential biomarkers predicting freezability and for the development of new additives and protocols [ 80 ].…”
Section: Semenmentioning
confidence: 99%
“…Targeted enrichment of valine was developed as per and was proved to be effective [ 78 ]. Ribeiro et al showed the genetically determined aquaporins expression difference may render the variation in cryotolerance [ 79 ]. These results are important for the identification of potential biomarkers predicting freezability and for the development of new additives and protocols [ 80 ].…”
Section: Semenmentioning
confidence: 99%
“…Ducha et al (2013) menyatakan, bahwa kerusakan dapat terjadi akibat adanya cold shock yang menyebabkan susunan lipid membran mengalami perubahan. Ribeiro et al (2022) menambahkan, bahwa proses pembekuan dapat merusak spermatozoa karena terbentuknya kristal es dalam sel akibat proses pengeluaran air secara intraseluler yang dapat menyebabkan kerusakan pada spermatozoa. Oleh sebab itu, untuk memperkecil kemungkinan kerusakan struktur sel spermatozoa saat penyimpanan, maka perlu ditambahkan suatu media yang disebut pengencer.…”
Section: Pendahuluanunclassified
“…Additionally, the Na + /K + -ATPase pump involving the ATPase Na + /K + Transporting Subunit Alpha 1 ( ATP1a1 ) located at the basal membrane of the TE facilitates the movement of Na + into the blastocoel through the TE, creating an osmotic pressure gradient that leads to fluid accumulation and blastocoel formation ( Kidder, 2002 ; Barcroft et al, 2003 ; Barcroft et al, 2004 ). Furthermore, aquaporins (AQPs), membrane transporters, play a significant role in water transport ( Edashige et al, 2007 ; Ribeiro et al, 2022 ). Previous studies have demonstrated that inhibition of AQPs suppresses blastocoel expansion, indicating their role in transporting water across the TE ( Barcroft et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%